Analysis Of Firm Value In The Property And Real Estate Sub-Sector On The Indonesia Stock Exchange - Zahro, Aziza; Suwaidi, Rahman Amrullah (UNIVERSITAS PAKUAN, 2025)
Abstract. In the property and real estate industry, firm value is a crucial indicator that reflects investors' level of confidence in a company's sustainable long-term potential. The purpose of this study is to examine the influence of firm growth and liquidity on firm value, with capital structure serving as a moderating variable. The research method employs a quantitative approach, utilizing a secondary publication dataset comprising corporate financial statements from the property and real estate subsectors listed on the Indonesia Stock Exchange for the 2020-2023 period. The purposive sampling technique was applied to obtain 68 research samples from a population of 92 issuers. Data analysis used moderation regression analysis using IBM SPSS software version 25. The findings of the study prove that the firm's growth contributes negatively to firm value and that liquidity does not contribute to firm value. In addition, the capital structure plays a role in strengthening or weakening firm growth on firm value. However, the capital structure does not play a role in strengthening or weakening the liquidity of a firm's value.